Maritime-Based Ecotourism: A Simple Educational Model for Yacht Passengers to Enhance Marine Environment Sustainability - Dede Ardian; Riki Wanda Putra; Herdi Santoso (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2026)
The rapid growth of maritime tourism in Banyuwangi, Indonesia, presents both significant economic opportunities and increasing pressure on fragile marine ecosystems. This article is framed as a conceptual and experiential case study that examines the role of passenger education in promoting marine environmental sustainability within yacht tourism operations. Drawing on participatory observation grounded in the author’s professional experience as a yacht captain, the study identifies recurring patterns of environmentally detrimental passenger behaviour and develops a simple educational intervention embedded within routine operational practices. The proposed 5-Minute Pre-Sail Briefing model integrates concise sustainability messages into standard operating procedures, with emphasis on waste prevention, coral reef protection, and respectful interaction with marine life. The findings represent observational insights rather than empirical validation, suggesting that brief, context-specific educational communication has the potential to encourage pro-environmental behaviour among yacht passengers. Although the model is not intended to be generalisable, it demonstrates potential transferability to comparable small-scale maritime tourism contexts. Overall, this study underscores the importance of behavioural and educational strategies as complementary elements of sustainable maritime transport.